Find the sum of the absolute values of all possible solutions to the equation x x 2 − 5 x + 6 = 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i did it in the same way but it appears to be more of a number theory problem
To have a b = 1 , we may have one of three possibilities; (1) a = 1 , (2) a = − 1 with b even or (3) b = 0 , provided a = 0 .
Case (1): we have x = 1 as a solution trivially.
Case (2): we take x = − 1 and verify that the exponent is even:
( − 1 ) 2 − 5 ( − 1 ) + 6 = 1 + 5 + 6 = 1 2 , which is even, so x = − 1 is a solution.
Case (3): we solve x 2 − 5 x + 6 = 0 . Factoring, ( x − 2 ) ( x − 3 ) = 0 , giving x = 2 and x = 3 , which are both nonzero, thus also solutions.
We answer: ∣ − 1 ∣ + ∣ 1 ∣ + ∣ 2 ∣ + ∣ 3 ∣ = 1 + 1 + 2 + 3 = 7
Solution Outline:
Taking log on both sides we get ( x 2 − 5 x + 6 ) l n ( x ) = 0
So either we have x 2 − 5 x + 6 = 0 or l n ( ∣ x ∣ ) = 0.
But ln(-1) is complex.
Log in to reply
Evaluate the whole thing at x=1 ( ( − 1 ) 2 − 5 ( − 1 ) + 6 ) l n ( − 1 ) = 1 2 i π and take the antilog of 12i*pi e 1 2 i π = 1
so -1 is a solution too
Log in to reply
Log in to reply
@Vinay Sipani – No, you're wrong. Its not always like that. Complex numbers work differently :)
@Vinay Sipani – Well, the logarithm function isn't exactly the inverse of a complex exponential.
Log in to reply
@Justin Quintos – Consider this problem
Here,-7 is not considered as it is complex but it could be shown that the inverse is not true and hence -7 can be considered.
Log in to reply
@Vinay Sipani – –7 is indeed a solution to the equation (using complex analysis concepts).
I can provide here, if you want, a step-by-step solution as to how substituting –7 in the left side equals 16
Log in to reply
@Justin Quintos – You are right...
The answer to that question must be changed...
Problem Loading...
Note Loading...
Set Loading...
3 cases.
1 . x = 0 , x 2 − 5 x + 6 = 0 gives x = 2 , 3 .
2 . x = 1 , x 2 − 5 x + 6 = 2 .
3 . x = − 1 , x 2 − 5 x + 6 = 1 2 which is even.
Answer: 2 + 3 + 1 + 1 = 7 .